PII1: a protein involved in starch initiation that determines granule number and size in Arabidopsis chloroplast. Issue 1 (28th July 2018) - Vandromme, Camille; Spriet, Corentin; Dauvillée, David; Courseaux, Adeline; Putaux, Jean‐Luc; Wychowski, Adeline; Krzewinski, Frédéric; Facon, Maud; D'Hulst, Christophe; Wattebled, Fabrice
Summary: The initiation of starch granule formation is still poorly understood. However, the soluble starch synthase 4 (SS4) appears to be a major component of this process since it is required to synthesize the correct number of starch granules in the chloroplasts of Arabidopsis thaliana plants. A yeast two‐hybrid screen allowed the identification of several putative SS4 interacting partners. We identified the product of At4g32190 locus as a chloroplast‐targeted PROTEIN INVOLVED IN STARCH INITIATION (named PII1). Arabidopsis mutants devoid of PII1 display an alteration of the starch initiation process and accumulate, on average, one starch granule per plastid instead of the five to seven granules found in plastids of wild‐type plants. These granules are larger than in wild‐type, and they remain flat and lenticular. pii1 mutants display wild‐type growth rates and accumulate standard starch amounts. Moreover, starch characteristics, such as amylopectin chain length distribution, remain unchanged. Our results reveal the involvement of PII1 in the starch priming process in Arabidopsis leaves through interaction with SS4.